Interactions between helminths and tuberculosis infections: Implications for tuberculosis diagnosis and vaccination in Africa. - Simeon I Cadmus; Victor O Akinseye; Babafemi O Taiwo; Elena O Pinelli; Dick van Soolingen; Shelley G Rhodes (Public Library of Science (PLoS), 2020)
Africa is the second most populous continent and has perennial health challenges. Of the estimated 181 million school aged children in sub-Saharan Africa (SSA), nearly half suffer from ascariasis, trichuriasis, or a combination of these infections. Coupled with these is the problem of tuberculosis (TB) caused by Mycobacterium tuberculosis (Mtb) infection, which is a leading cause of death in the region. Compared to the effect of the human immunodeficiency virus on the development of TB, the effect of chronic helminth infections is a neglected area of research, yet helminth infections are as ubiquitous as they are varied and may potentially have profound effects upon host immunity, particularly as it relates to TB infection, diagnosis, and vaccination. Protection against active TB is known to require a clearly delineated T-helper type 1 (Th1) response, while helminths induce a strong opposing Th2 and immune-regulatory host response. This Review highlights the potential challenges of helminth-TB co-infection in Africa and the need for further research.